Hydrophobic confinement metal nano-catalyst, preparation method and application

By introducing a hydrophobic structure on the surface of the catalyst, a super-stable hydrophobic confined nanometal catalyst is formed, which solves the problem of poor stability of CO2 electroreduction catalysts in the prior art under high current density, and achieves efficient CO2 reduction and salt crystallization inhibition. It has wide industrial application prospects.

CN119243222APending Publication Date: 2025-01-03BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411518834.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing CO2 electroreduction catalysts are difficult to maintain high selectivity and stability for a long time under high current density, and are prone to inactivation due to salt crystallization problems.

Method used

The electrochemical deposition technology is used to introduce a hydrophobic structure on the surface of the catalyst, and the hydrophobic conductive substrate is combined with the conductive nanofiber to form a super-stable hydrophobic confined nanometal catalyst, which inhibits the formation of salt crystallization and improves the stability of the catalyst.

Benefits of technology

The stability and selectivity of the catalyst are significantly improved at high current density, prolong the service life of the catalyst, and effectively inhibit the formation of salt crystals, ensuring excellent performance under complex reaction conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243222A_ABST
    Figure CN119243222A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrophobic confinement nano-metal catalyst, a preparation method and application. The method comprises the following steps: preparing a conductive nanofiber and hydrophobic high-molecular polymer mixed solution; loading a conductive nanofiber and hydrophobic high-molecular polymer mixed solution on a substrate to obtain a hydrophobic conductive substrate; preparing a metal salt solution; the preparation method comprises the following steps: putting a hydrophobic conductive substrate into a metal salt solution, and simultaneously performing electrochemical reduction to obtain the catalyst, the preparation method of the hydrophobic confinement catalyst is simple, mild in condition and easy to operate. In the electrochemical reduction preparation process of the catalyst, metal particles are loaded on the conductive nanofibers around the hydrophobic high-molecular polymer in situ, so that the nano metal catalyst with a hydrophobic confinement environment is formed. When the hydrophobic confinement nano-metal catalyst is applied to the process of electrocatalytic reduction of CO2, the hydrophobic confinement nano-metal catalyst has a stable hydrophobic surface, and salt crystallization can be effectively inhibited, so that excellent electrocatalytic reduction performance and stability of CO2 are realized under high current density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalysts, in particular to technologies related to electrocatalytic CO2 reduction, and specifically provides a hydrophobic confined nanometal catalyst, a preparation method and an application thereof. The catalyst can maintain high selectivity and high stability for a long time at high current density, effectively overcoming the problem of salt crystallization in the CO2 electroreduction process. Background Art

[0002] Excessive CO2 emissions have attracted widespread attention worldwide, and the resource utilization of CO2 has become one of the key ways to solve this problem. Using renewable electricity to electrocatalytically reduce CO2 (CO2RR) to high-value-added multi-carbon chemicals (C 2+ ) is an effective method and has become a research hotspot in the field of catalysis in recent years. However, the electroreduction of CO2 to C 2+ In the process of producing products, there are challenges such as competition from hydrogen evolution side reactions, complex intermediates, and difficult carbon-carbon coupling. Therefore, the development of efficient electrocatalysts has become a key research direction in the field of CO2RR.

[0003] Studies have shown that metal catalysts can effectively electrocatalyze the reduction of CO2 to CO, formic acid, ethylene, ethanol, etc., but there are still problems such as low product selectivity, poor stability, and difficulty in maintaining high current density and high selectivity for a long time. The latest research points out that the excessive aggregation of electrolyte cations on the catalyst surface under electric field induction and the precipitation of salt crystals are one of the key reasons for the failure of metal catalysts. These salt crystals will cover the catalytic active sites and cause the disappearance of the "gas-liquid-solid" three-phase interface on the catalyst surface, ultimately leading to catalyst deactivation.

[0004] In recent years, some results have been achieved in regulating the hydrophobicity of the catalyst surface through methods such as functional modification and morphology control. For example, Professor Yang Peidong et al. (Nat. Energy 2020, 5, 1032) proposed an ordered ligand layer modification strategy to form a hydrophobic layer on the catalyst surface, and used the pseudocapacitive properties of the ligand layer to regulate the insertion of desolvated cations, inhibit the excessive aggregation of cations to form salt crystals, and promote the activation of CO2. The prepared Ag-NOLI catalyst was used in 1 M KHCO3 electrolyte at 400 mA cm -2The Chinese patent with application number 202010150344.6 loads the copper fluoride precursor on the gas diffusion layer, and obtains the fluorine-modified hydrophobic copper catalyst through electroreduction, which can electrocatalyze the reduction of CO2 to C2+ products at ampere current density, with a Faraday efficiency of up to 80%. Although some progress has been made in inhibiting salt crystallization, it is still a global problem to achieve long-term and stable electrocatalysis at high current density, overcome the problem of salt crystallization and maintain a hydrophobic catalytic microenvironment. Summary of the invention

[0005] In view of the deficiencies in the prior art, and the problem of insufficient catalyst stability and activity in the electrochemical reduction reaction of CO2 in the prior art, the present invention proposes a hydrophobic confined nanometal catalyst, a preparation method and an application. The method is a method for preparing an ultra-stable hydrophobic confined nanometal catalyst. The application is the application of a hydrophobic confined nanometal catalyst in electrocatalytic CO2 reduction. The method uses electrochemical deposition technology to accurately control the morphology and distribution of nanometal particles, and introduces a hydrophobic structure on the catalyst surface to significantly improve the activity and stability of the catalyst during the electroreduction of CO2. The catalyst provided by the present invention can maintain efficient electrocatalytic performance for a long time at high current density, effectively inhibit the formation and accumulation of salt crystals, thereby ensuring excellent performance under complex reaction conditions. This new catalyst can not only improve the selectivity of CO2 reduction to high value-added chemicals, but also extend the service life of the catalyst, and has broad industrial application prospects.

[0006] The objectives of the present invention are achieved through the following technical solutions:

[0007] A method for preparing a hydrophobic confined nanometal catalyst comprises the following steps:

[0008] (1) uniformly mixing the hydrophobic polymer and the conductive nanofibers to form a mixed solution with good dispersibility and stability;

[0009] (2) The mixed solution is uniformly loaded on a substrate material, and a substrate having hydrophobicity and conductivity is prepared by treatment (such as drying or curing), which is called a hydrophobic conductive substrate;

[0010] (3) According to the requirements of the target catalyst metal component, prepare the corresponding metal salt solution to ensure that the metal ion concentration in the solution is appropriate to achieve efficient electrochemical deposition;

[0011] (4) Immersing the hydrophobic conductive substrate in the metal salt solution obtained in step (3), and applying electrochemical reduction conditions to generate nano-metal particles in situ on the surface of the substrate through an electrochemical deposition process. These nano-particles are evenly distributed on the surface of the hydrophobic conductive substrate, forming a nano-metal catalyst with ultra-stable hydrophobic confinement.

[0012] In the present invention, placing the hydrophobic conductive substrate in the solution obtained in step (3) means immersing the hydrophobic conductive substrate in the solution obtained in step (3).

[0013] Furthermore, in step (1), the concentration of the hydrophobic polymer is 0.001 mol L -1 ~ 3 mol L -1 For example, the concentration of the hydrophobic polymer dispersion is 0.001 mol L -1 , 0.005 mol L -1 , 0.01 mol L -1 , 0.05 mol L -1 , 0. 1 mol L -1 , 0.5 mol L -1 , 1 mol L -1 , 1.5 mol L -1 , 2 mol L -1 , 2. 5 molL -1 or 3 mol L -1 The concentration of the hydrophobic polymer is preferably 0.1 mol L -1 .

[0014] Furthermore, in step (1), the hydrophobic polymer includes at least one of polyethylene, polypropylene, polytrifluoroethylene, polytetrafluoroethylene, polyol ester, polyurethane, polyacrylic acid, and polysulfone. The hydrophobic polymer is preferably polypropylene.

[0015] Furthermore, in step (1), the concentration of the conductive nanofibers is 0.001 g L -1 ~ 3 g L -1 For example, the concentration of the conductive nanofibers is 0.001 g L -1 , 0.005 g L -1 , 0.01 g L -1 , 0.05 g L -1 , 0.1 g L -1 , 0.5 g L -1 , 1g L -1 , 1.5 g L -1 , 2 g L -1 , 2.5 g L -1 or 3 g L -1 The concentration of the conductive nanofibers is preferably 0.01 g L -1 .

[0016] Furthermore, in step (1), the conductive nanofibers include carbon nanotubes (including single-walled carbon nanotubes and / or multi-walled carbon nanotubes), carbon fibers, carbon cloth, metal nanofibers (wherein the metal includes one or more of manganese, iron, nickel, copper, cobalt, zinc, gold and silver), and the conductive nanofibers are preferably carbon fibers.

[0017] Furthermore, in step (2), the conductive nanofibers and the hydrophobic polymer loading amount is 0.01 mg / cm -2 ~ 100 mg cm -2 For example, the conductive nanofibers and the hydrophobic polymer loading is 0.01 mg cm -2 , 0.05 mg cm -2 , 0.1 mg cm -2 , 0.5 mg cm -2 , 1 mg cm -2 , 5 mg cm -2 , 10 mg cm -2 , 50 mg cm -2 or 100 mg cm -2 The conductive nanofibers and hydrophobic polymer loading is preferably 1 mg cm -2 .

[0018] Furthermore, in step (2), the substrate includes one or more of carbon paper, carbon cloth, metal foil, metal mesh and metal foam (wherein the metal includes one or more of manganese, iron, nickel, copper, cobalt, zinc, gold and silver).

[0019] Furthermore, in step (3), the concentration of the metal salt solution is 0.001 mol L -1 ~ 3 mol L -1 For example, the concentration of the metal salt solution is 0.001 mol L -1 , 0.005 mol L -1 , 0.01 mol L -1 , 0.05 mol L -1 , 0.1 mol L -1 , 0.5 mol L -1 , 1 mol L -1 , 1.5 mol L -1 , 2 mol L -1 , 2. 5 mol L -1 or 3 mol L -1 The concentration of the metal salt solution is preferably 0.1 mol L -1 .

[0020] Further, in step (3), the metal salt (wherein the metal includes one or more of manganese, iron, nickel, copper, cobalt, zinc, gold and silver) includes one or more of chloride, bromide, fluoride, iodide, carbonate, nitrate, tartrate, carboxylate, sulfate, sulfite, ketoate and amino acid salt. The metal salt is preferably sulfate. For example, the metal salt is copper sulfate, copper acetylacetonate, nickel sulfate, chloroauric acid, copper formate or silver nitrate.

[0021] Furthermore, in step (4), the electrochemical reduction condition is constant current or constant voltage. The constant voltage range is -0.3 ~ -2.0 V (relative to standard hydrogen electrode (vs RHE)). The constant current range is 0.005 ~ 0.2 A cm -2 For example, the constant potential range is -0.3 V, -0.5 V, -1 V, -1.5 V or -2.0 V (vs. standard hydrogen electrode (vs RHE)); the constant current range is 0.005 A cm -2 , 0.01 A cm -2 , 0.05 A cm -2 , 0.1 A cm -2 , 0.15 A cm -2 or 0.2 A cm -2 .

[0022] In the catalyst prepared by any of the above methods, metal nanoparticles are loaded on the conductive nanofibers coated with hydrophobic polymers by in-situ deposition to form a hydrophobic confined nanometal catalyst structure. In the hydrophobic confined nanometal catalyst, the metal loading is 0.002 mg cm -2 ~1 mg cm -2 (e.g., 0.002 mg cm -2 , 0.005mg cm -2 , 0.01 mg cm -2 , 0.02 mg cm -2 , 0.03 mg cm -2 , 0.04 mg cm -2 , 0.06 mg cm -2 , 0.08 mgcm -2 , 0.1 mg cm -2 , 0.3 mg cm -2 , 0.6 mg cm -2 , 0.9 mg cm -2 or 1 mg cm -2 ).

[0023] Application of a catalyst prepared by any of the methods described above in the electrocatalytic reduction of CO2: the prepared hydrophobic confined nanometal catalyst is used as the cathode, a platinum sheet or iridium oxide is used as the anode, and a saturated Ag / AgCl electrode is used as the reference electrode; CO2 is passed into the cathode and a negative potential is applied for electrolysis to obtain a reduction product.

[0024] The CO2 gas flow rate is 1-100 mL min -1 The electrolyte includes at least one of LiOH, NaOH, KOH, CsOH, NaHCO3, KHCO3 and CsHCO3, and the electrolyte concentration is 0.1 to 10 mol L -1 ; Negative potential of -0.2 to -2.5 V (vs. standard hydrogen electrode (vs RHE)) or -1 to -10 V (two-electrode system, no reference electrode). For example, the electrolyte concentration is 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 mol L -1 .

[0025] The present invention has the following advantages:

[0026] (1) The catalyst preparation process provided by the present invention is simple and easy to operate, the operating conditions are mild, and it has wide applicability and is suitable for large-scale production and practical application.

[0027] (2) During the electrochemical reduction preparation process, metal nanoparticles are precisely loaded on the hydrophobic polymer-coated conductive nanofibers through in-situ deposition, forming a unique hydrophobic confined nanometal catalyst structure. This design not only enhances the stability of the catalyst, but also effectively improves its performance under complex reaction conditions.

[0028] (3) In the application of electrocatalytic CO2 reduction, the hydrophobic confined nanometal catalyst successfully inhibited the formation and accumulation of salt crystals during the electrolysis process due to its stable hydrophobic surface, thereby demonstrating excellent electrocatalytic performance and long-term stability at high current density, providing a reliable technical guarantee for efficient CO2 reduction. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope image of the hydrophobic confined nano-copper catalyst prepared in Example 1;

[0030] Figure 2 This is a performance diagram of electrocatalytic reduction of CO2 by the hydrophobic confined nano-copper catalyst prepared in Example 1;

[0031] Figure 3 The stability of the hydrophobic confined nano-copper catalyst prepared in Example 1 for electrocatalytic reduction of CO2. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. However, the following embodiments are limited to explaining the present invention, and the protection scope of the present invention should include the entire contents of the claims, and through the description of the following embodiments, those skilled in the art can fully implement the entire contents of the claims of the present invention.

[0033] Embodiment 1:

[0034] (1) Polypropylene, carbon nanotubes and deionized water were mixed evenly to prepare a mixture of polypropylene (manufacturer: Macklin, product number: P909210, weight average molecular weight: 250,000) and carbon nanotubes (type: single-walled carbon nanotubes, manufacturer: Pioneer Nano, product number: XFS30); the concentration of polypropylene in the mixture was 0.1 mol L -1 , the carbon nanotube concentration is 0.01 g L -1 ;

[0035] (2) The mixture of polypropylene and carbon nanotubes was loaded onto carbon paper (Toray, Japan, TGPH060) by spraying (loading amount was 1 mg cm -2 ), dried at 60 °C for 24 h to obtain hydrophobic carbon paper;

[0036] (3) Mix copper sulfate and deionized water evenly to a concentration of 0.1 mol L -1 of copper sulfate solution;

[0037] (4) Place the hydrophobic carbon paper in the copper sulfate solution obtained in step (3) and apply 0.1 A cm -2 The nano-copper catalyst was obtained after 5 min of electrochemical reduction. The hydrophobic confined nano-copper catalyst (copper loading: 0.02 mg cm -2 ).

[0038] Figure 1 This is a scanning electron microscope image of the hydrophobic confined nano-copper catalyst prepared in Example 1. The nano-copper particles are in situ loaded onto the carbon nanotubes surrounding the hydrophobic high molecular polymer, and the particle size is about 60-120 nm.

[0039] Figure 2This is the performance diagram of the electrocatalytic reduction of CO2 of the hydrophobic confined nano-copper catalyst prepared in Example 1. The gas pressure is 1 standard atmosphere and the temperature is room temperature (25°C). The prepared hydrophobic confined nano-copper catalyst is used as the cathode, the platinum sheet is used as the anode, and the saturated Ag / AgCl electrode is used as the reference electrode; 1 M KOH is used as the electrolyte, CO2 is passed into the cathode at a flow rate of 20 sccm, and a negative potential (-0.5 to -2.5 V vs RHE) is applied for electrolysis to obtain the reduction product. It can be seen that the hydrophobic confined nano-copper catalyst can electrocatalytically convert CO2 into a variety of high value-added C2 products with a Faraday efficiency of 90%.

[0040] Figure 3 This is a test diagram of the electrocatalytic reduction of CO2 stability of the hydrophobic confined nano-copper catalyst prepared in Example 1. The gas pressure is 1 standard atmosphere and the temperature is room temperature (25°C). The prepared hydrophobic confined nano-copper catalyst is used as the cathode, the platinum sheet is used as the anode, and the saturated Ag / AgCl electrode is used as the reference electrode; 0.05 M KHCO3 is used as the electrolyte, CO2 is passed into the cathode at a flow rate of 20 sccm, and a negative potential is applied for electrolysis to obtain the reduction product. It can be seen that the hydrophobic confined nano-copper catalyst can reduce CO2 at 200 mA cm -2 The catalytic performance was stable for more than 1000 h at a current density of 1.54 W / m and 2.54 W / m, with no obvious attenuation.

[0041] Embodiment 2:

[0042] (1) Polysulfone (manufacturer: Macklin, catalog number: P856835, weight average molecular weight: 80,000), carbon nanotubes (type: single-walled carbon nanotubes, manufacturer: Pioneer Nano, catalog number: XFS30) and deionized water were mixed evenly to prepare a polysulfone and carbon nanotube mixed solution; the polysulfone concentration in the mixed solution was 0.1 mol L -1 , the carbon nanotube concentration was 0.05 g L -1 ;

[0043] (2) The polysulfone and carbon nanotube mixture was sprayed onto carbon paper (Toray, Japan, TGPH060) (loading amount was 2 mg cm -2 ), dried at 80 °C for 12 h to obtain hydrophobic carbon paper;

[0044] (3) Mix copper acetylacetonate and deionized water evenly to a concentration of 0.1 mol L -1 of copper acetylacetonate solution;

[0045] (4) Place the hydrophobic carbon paper in the copper acetylacetonate solution obtained in step (3) and apply 0.1 A cm -2The nano-copper catalyst was obtained after 5 min of electrochemical reduction. -2 ). The gas pressure was 1 standard atmosphere and the temperature was room temperature (25°C). The prepared hydrophobic confined nano-copper catalyst was used as the cathode, the platinum sheet was used as the anode, and the saturated Ag / AgCl electrode was used as the reference electrode. 1 M KOH was used as the electrolyte. CO2 was passed into the cathode at a flow rate of 20 sccm. A negative potential (-0.5 to -2.5 V vs RHE) was applied for electrolysis to obtain the reduction product. The selectivity of the multi-carbon product exceeded 80%.

[0046] Embodiment 3:

[0047] (1) Polytrifluoroethylene, carbon fiber and deionized water were mixed evenly to prepare a mixture of polytrifluoroethylene (manufacturer: Macklin, product number: P758976, mass concentration: 45%) and carbon fiber (manufacturer: Pioneer Nano, product number: XFZ08, diameter: 60 μm); the concentration of polytrifluoroethylene in the mixture was 0.1 mol L -1 , the carbon fiber concentration is 0.02 g L -1 ;

[0048] (2) The mixture of polytrifluoroethylene and carbon fiber was sprayed onto carbon paper (Toray, Japan, TGPH060) (loading amount was 3 mg cm -2 ), dried at 40 °C for 48 h to obtain hydrophobic carbon paper;

[0049] (3) Mix silver nitrate and deionized water evenly to a concentration of 1 mol L -1 of silver nitrate solution;

[0050] (4) Place the hydrophobic carbon paper in the silver nitrate solution obtained in step (3) and apply 0.1 A cm -2 The hydrophobic confined nanosilver catalyst (silver loading: 0.03 mg cm) was obtained after 3 min of electrochemical reduction. -2 ). The gas pressure was 1 standard atmosphere and the temperature was room temperature (25°C). The prepared hydrophobic confined nanosilver catalyst was used as the cathode, the platinum sheet was used as the anode, and the saturated Ag / AgCl electrode was used as the reference electrode. 1 MKHCO3 was used as the electrolyte. CO2 was passed into the cathode at a flow rate of 20 sccm. A negative potential (-0.5 to -2.5 V vs RHE) was applied for electrolysis to obtain the reduction product. The carbon monoxide selectivity exceeded 90%.

[0051] Embodiment 4:

[0052] (1) Polyurethane, carbon fiber and deionized water were mixed evenly to prepare a polyurethane (manufacturer: Macklin, product number: A909856, solid content: 40%) and carbon fiber mixed solution; the polyurethane concentration in the mixed solution was 0.5 mol L -1 , the carbon fiber concentration was 0.5 g L -1 ;

[0053] (2) The polyurethane and carbon fiber mixture was loaded onto a metal nickel mesh (manufacturer: Sigma, thickness: 200 μm) (loading amount: 5 mg cm -2 ), dried at 25 °C for 48 h to obtain a hydrophobic nickel mesh;

[0054] (3) Mix nickel sulfate and deionized water evenly to a concentration of 0.2 mol L -1 of nickel sulfate solution;

[0055] (4) Place the hydrophobic nickel mesh in the nickel nitrate solution obtained in step (3) and apply 0.05 A cm -2 The hydrophobic confined nano-nickel catalyst (nickel loading: 0.03 mg cm) was obtained after 5 min of electrochemical reduction. -2 ). The gas pressure was 1 standard atmosphere and the temperature was room temperature (25°C). The prepared hydrophobic confined nano-nickel catalyst was used as the cathode, the platinum sheet was used as the anode, and the saturated Ag / AgCl electrode was used as the reference electrode. 0.5 M KHCO3 was used as the electrolyte. CO2 was passed into the cathode at a flow rate of 20 sccm. A negative potential (-0.5 to -2.5 V vs RHE) was applied for electrolysis to obtain the reduction product. The carbon monoxide selectivity exceeded 90%.

[0056] Embodiment 5:

[0057] (1) Polyacrylic acid, silver nanofibers and deionized water were mixed evenly to prepare a mixed solution of polyacrylic acid (manufacturer: Inotech, product number: A13519, average Mv: 450000) and silver nanofibers (manufacturer: Pioneer Nano, product number: XFDZSN, purity: 99.99%); the concentration of polyacrylic acid in the mixed solution was 0.3 mol L -1 , the silver nanofiber concentration was 0.02 g L -1 ;

[0058] (2) The mixture of polyacrylic acid and silver nanofibers was loaded onto carbon cloth (manufacturer: Carbon Energy, product number: W0S1009F) (loading amount: 3 mg cm -2 ), dried at 80 °C for 12 h to obtain a hydrophobic carbon cloth;

[0059] (3) Mix chloroauric acid and deionized water evenly to a concentration of 0.1 mol L -1 of chloroauric acid solution;

[0060] (4) Place the hydrophobic carbon in the chloroauric acid solution obtained in step (3) and apply 0.05 A cm -2 The hydrophobic confined nano-gold catalyst was obtained after electrochemical reduction for 5 min. The hydrophobic confined nano-gold catalyst was obtained. The gas pressure was 1 standard atmosphere and the temperature was room temperature (25°C). The prepared hydrophobic confined nano-gold catalyst was used as the cathode, the platinum sheet was used as the anode, and the saturated Ag / AgCl electrode was used as the reference electrode; 0.2 M KHCO3 was used as the electrolyte, CO2 was passed into the cathode at a flow rate of 40 sccm, and a negative potential (-0.5 to -2.5 V vs RHE) was applied for electrolysis to obtain the reduction product, and the carbon monoxide selectivity exceeded 90%.

[0061] Application of the prepared hydrophobic confined nanometal catalyst in electrocatalytic reduction of CO2:

[0062] The hydrophobic confined nano-copper catalyst prepared in Example 1 was used as the cathode and iridium oxide was used as the anode to carry out the reaction in a membrane electrode electrolyzer (manufacturer: Gaoss Union, model: 101018); the gas pressure was 1 standard atmosphere and the temperature was room temperature (25°C); the anode chamber was 0.05 mol L -1 of potassium bicarbonate electrolyte; CO2 was added at 20 mL min -1 The cathode chamber was continuously charged with -200 mA cm -2 By electrolyzing with a constant current, a variety of high value-added C2 products (including ethylene with a Faraday efficiency of up to 70% and a total Faraday efficiency of C2 products exceeding 90%) were produced, and there was no obvious voltage fluctuation after 1000 hours of continuous reduction.

[0063] The present invention does not elaborate on some of the common technologies of those skilled in the art. The above-described embodiments are only descriptions of preferred implementations of the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementations described. Without departing from the design spirit of the present invention, various modifications and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the scope of protection determined by the claims of the present invention.

Claims

1. A method for preparing a hydrophobic confined nanometal catalyst, characterized in that: The following steps are involved: (1) uniformly mixing the hydrophobic polymer and the conductive nanofibers to form a mixed solution; (2) uniformly loading the mixed solution onto a substrate material, and preparing a substrate having hydrophobicity and conductivity by treatment (the treatment being drying or curing), which is referred to as a hydrophobic conductive substrate; (3) preparing a corresponding metal salt solution according to the requirements of the target catalyst metal component; (4) Immersing the hydrophobic conductive substrate in the metal salt solution obtained in step (3) and applying electrochemical reduction conditions to in-situ generate nano-metal particles on the surface of the substrate through an electrochemical deposition process.

2. The method according to claim 1, characterized in that In step (1), the concentration of the hydrophobic polymer in the mixed solution is 0.001 mol L -1 ~ 3 mol L -1 ; Preferably, the hydrophobic high molecular polymer includes at least one of polyethylene, polypropylene, polytrifluoroethylene, polytetrafluoroethylene, polyol ester, polyurethane, polyacrylic acid and polysulfone.

3. The method according to claim 1, characterized in that: In step (1), the concentration of the conductive nanofibers in the mixed solution is 0.001 g L -1 ~ 3 g L -1 ; Preferably, the conductive nanofibers include at least one of carbon nanotubes (including single-walled carbon nanotubes and / or multi-walled carbon nanotubes), carbon fibers, carbon cloth and metal nanofibers (wherein the metal includes one or more of manganese, iron, nickel, copper, cobalt, zinc, gold and silver).

4. The method according to claim 1, characterized in that: In step (2), the conductive nanofibers and the hydrophobic polymer loading on the substrate material is 0.01 mg cm -2 ~ 100 mg cm -2 ; Preferably, the substrate comprises one or more of carbon paper, carbon cloth, metal foil, metal mesh and metal foam (wherein the metal comprises one or more of manganese, iron, nickel, copper, cobalt, zinc, gold and silver).

5. The method according to claim 1, characterized in that In step (3), the concentration of the metal salt solution is 0.001 mol L -1 ~ 3 mol L -1 ; Preferably, the metal salt (wherein the metal comprises one or more of manganese, iron, nickel, copper, cobalt, zinc, gold and silver) comprises one or more of chloride, bromide, fluoride, iodide, carbonate, nitrate, tartrate, carboxylate, sulfate, sulfite, ketoate and amino acid salt.

6. The method according to claim 1, characterized in that In step (4), the electrochemical reduction condition is constant current or constant voltage; the constant voltage range is -0.3 ~ -2.0 V (relative to standard hydrogen electrode (vs RHE)), and the constant current range is 0.005 ~ 0.2 A cm -2 .

7. A catalyst prepared by the method according to any one of claims 1 to 6, characterized in that Metal nanoparticles are loaded on the conductive nanofibers coated with hydrophobic polymers through in-situ deposition to form a hydrophobic confined nanometal catalyst structure.

8. Use of the catalyst prepared by the method according to any one of claims 1 to 6 in electrocatalytic reduction of CO2, characterized in that: The prepared hydrophobic confined nanometal catalyst is used as a cathode, a platinum sheet or iridium oxide is used as an anode, and a saturated Ag / AgCl electrode is used as a reference electrode; CO2 is passed into the cathode and a negative potential is applied for electrolysis to obtain a reduction product.